Население Крыма в середине III-IV вв. - Айбабин, А.И. (Материалы по археологии, истории и этнографии Таврии, 1996)
Migrations which began as a result of military activities of the Germans in the end of the first half of the 3d century "radically changed the ethnopolitical situation on the peninsula. The Roman Empire had to abandon any presence in the Crimea. Bosporos Kingdom had been under the control of the Germanic tribes for more than 20 years. They, together with allied Alans, destroyed the Late-Scythian state and the major part of its population. Only the Sarmatians, who lived in the lower reaches of the Belbek River and„ in the region of the Bodrak River, managed to survive. In the South-Western Crimea the Alans and Germans dominated from 250s. The Alans settled in the European part of Bosporos Kingdom and penetrated to Chersonesos. In 260s a deep crisis took place there, probably, it was caused by the destruction of an important partner of the Late-Scythian state, departure of the Roman Army and seizure of Black Sea communications by the Germans.